Han Chinese family with early‐onset Parkinson's disease carries novel compound heterozygous mutations in the PARK2 gene - Ting Huang; Chen‐Yu Gao; Liang Wu; Peng‐Yu Gong; Ji‐Zheng Wang; You‐Yong Tian; Ying‐Dong Zhang (Brain and Behavior, 2019)
Abstract Purpose To identify deletions, duplications, and point mutations in 55 previously reported genes associated with Parkinson's disease (PD) and certain genes associated with tremor, spinocerebellar ataxia, and dystonia in a Han Chinese pedigree with early‐onset Parkinson's disease (EOPD). Patients and Methods Clinical examinations and genomic analyses were performed on six subjects belonging to three generations of a Han Chinese family. Target region capture and high‐throughput sequencing were used to screen these genes associated with PD, tremor, spinocerebellar ataxia, and dystonia. The multiplex ligation‐dependent probe amplification (MLPA) method was applied to detect rearrangements in PARK2 exons. Direct Sanger sequencing of samples from all subjects further verified the detected abnormal PRKRA, SPTBN2, and ATXN2 gene fragments. Results Two family members were diagnosed with PD based on the clinical manifestations, imaging analyses. PARK2 gene heterozygous deletion of exon 3 and heterozygous duplication of exon 6 were identified in them (II‐3 and 4). A single heterozygous deletion of exon 3 in PARK2 was detected in II‐5 and III‐10. A single duplication of exon 6 in PARK2 was detected in I1. Both the heterozygous mutation c.2834G>A (p. R945H) in exon 16 and the heterozygous mutation c.1924 C>T (p. R642W) in exon 14 of the SPTBN2 gene were identified in II‐3, II‐4, and III‐10. The heterozygous mutation c.2989 C>T (p. R997X) in exon 24 of the ATXN2 gene was detected in II‐4 and II‐5, and the heterozygous mutation c.170 C>A (p. S57Y) in exon 2 of the PRKRA gene was detected in II‐3, II‐4, and III‐10. Other mutations in some genes associated with PD, tremor, spinocerebellar ataxia, and dystonia were not detected. Conclusions Novel compound heterozygous mutations were identified in a Han Chinese pedigree and might represent a cause of EOPD.